Coherent atomic oscillations and resonances between coupled Bose-Einstein condensates with time-dependent trapping potential - Abdullaev, F. Kh [UNESP]; Kraenkel, Roberto André [UNESP] (American Physical Society (APS), 2000)
The atomic tunneling between two tunnel-coupled Bose-Einstein condensates (BECs) in a double-well time-dependent trap was studied. For the slowly varying trap, synchronization of oscillations of the trap with oscillations of the relative population was predicted. Using the Melnikov approach, the appearance of the chaotic oscillations in the tunneling phenomena between the condensates was confirmed.
Keywords: Atoms; Chaos theory; Electron resonance; Electron traps; Electron tunneling; Functions; Mathematical models; Numerical analysis; Oscillations; Quantum theory; Bose-Einstein condensates; Coherent atomic oscillations; Melnikov function approach; Quantum tunneling; Time dependent trapping potential; Electron gas